Expanding Fiscal Space for Healthcare System through Efficiency: A Qualitative Study from Iran - Firoozeh BAIRAMI; Amirhossein TAKIAN; Ali AKBARI SARI; Iraj HARIRCHI; Minoo Alipouri Sakha (Tehran University of Medical Sciences, 2020)
Background: Healthcare systems are always facing increasing public demands to provide better services. Therefore, countries always need more resources and are constantly seeking more fiscal space for health. Freeing up resources through improving efficiency can be a practical option for all settings, particularly countries with low resources. This study aimed to identify feasible options for expanding fiscal space through efficiency within Iran's healthcare system. Methods: This was a qualitative study. We conducted 29 semi-structured in-depth interviews with stakeholders at various levels of healthcare system in 2017 and 2018. We used mixed method (deductive and inductive) qualitative content analysis. Pre-defined themes extracted from literature and meanwhile new subthemes were developed and added to the initial framework. Results: We identified three main themes that affect the efficiency of healthcare system in Iran: administration, implementation, and monitoring. Problematic administration, inappropriate implementation and lack of good monitoring in healthcare initiatives may lead to inefficiencies and wasting resources. Recognizing these leakages in every healthcare system can free up some resources. Conclusion: Irrespective of their economic development, all countries may, to some extent, face limited resources to address ever-increasing needs in their healthcare systems. While generating new resources is not always possible, enhancing efficiency to expand fiscal space might be a feasible option. Healthcare systems should identify the leakages and respond to wastages with appropriate planning. Getting the most out of current resources is possible through proper administration, good implementation and a well-established monitoring system for healthcare initiatives.